Microbiologically influenced corrosion of stainless steel independent of sulfate-reducing bacteria - Wakai, Satoshi; Eno, Nanami; Mizukami, Hirotaka; Sunaba, Toshiyuki; Miyanaga, Kazuhiko; Miyano, Yasuyuki (Frontiers in Microbiology, 2022)
The presence and activities of microorganisms on metal surfaces can affect corrosion. Microbial communities after such corrosion incidents have been frequently analyzed, but little is known about the dynamics of microbial communities in biofilms on different types of stainless steels, such as austenitic, martensitic, and duplex stainless steels. Here, we conducted immersion experiments on 10 types of stainless steels in a freshwater environment, where microbiologically influenced corrosion was observed. During 22-month of immersion, severe localized corrosions were observed only on martensitic S40300 stainless steel. Microbial community analysis showed notable differences between non-corroded and corroded stainless steels. On the surfaces of non-corroded stainless steels, microbial communities were slowly altered and diversity decreased over time; in particular, relative abundance of Nitrospira sp. notably increased. Whereas microbial communities in corrosion products on corroded stainless steels showed low diversity; in particular, the family Beggiatoaceae bacteria, iron-oxidizing bacteria, and Candidatus Tenderia sp. were enriched. Furthermore, sulfur enrichment during localized corrosion was observed. Since there was no enrichment of sulfate-reducing bacteria, the sulfur enrichment may be derived from the presence of family Beggiatoaceae bacteria with intracellular sulfur inclusion. Our results demonstrated slow and drastic changes in microbial communities on the healthy and corroded metal surfaces, respectively, and microbial communities on the healthy metal surfaces were not affected by the composition of the stainless steel.